THE INVESTIGATION OF QUESTIONING MODIFICATIONS USED IN EFL CLASSROOM - Siti Sarah Fitriani; Cut Aulia Makhsum; Iskandar Abdul Samad (Journal of English Education, 2016)
Questions raised by a teacher as a part of teacher talk is important to stimulate students’ participation in English Foreign Language (EFL) classroom interaction. The questions posed by teachers in the classrooms are sometimes modified when they notice that the students have difficulties in understanding the questions. This study investigated four types of questioning modifications –repetition, narrowing by means of clues, rephrasing with alternative or “or-choice” questions and wait-time– proposed by Chaudron (1988) used by a teacher in one bilingual senior high school in Banda Aceh. Six sessions (altogether 480 minutes) of classroom observation were conducted. A dominant questioning modification type was indicated as a result of the analysis of video recordings from the observations. In addition, the reason of the teacher to use the dominant type of questioning modification is also discussed in this paper.